Structure, interaction, dynamics and solvent effects on the DNA-EcoRI complex in aqueous solution from molecular dynamics simulation. - Sen, S (1999)
A 0.7-ns molecular dynamics simulation of the DNA-EcoRI complex in a 7.0-A solvent shell indicated a stable behavior of the system. No significant evaporation or smearing of the solvent's outer boundary occurred. The structure and the intermolecular interactions were found to be well maintained during the simulation. The interaction pattern in the simulation was found to be very similar to that in the crystal structure. Most of the specific interactions between the DNA and the protein were found to be enhanced in the simulation compared to that in the crystal structure as a result of improved interaction geometry. The nonspecific interactions were found to be stronger than the specific ones. The specific interactions between the N7 atoms of Gua(4) or Ade(5) or Ade(6) and the protein were found to be present over almost the entire time of the simulation, whereas hydrogen bonds involving the amino groups of the Ade(5) and Ade(6) with the protein were found to be relatively weaker, with lower probability and shorter lifetime. The time evolution of the root mean square deviations of the DNA and the protein were highly correlated even at the later part of the simulation, showing the tight binding between them. Several long-lived water bridges were found between the DNA backbone atoms and the protein and also between the two protein monomers, which increased the overall stability of the complex. The two protein monomers were found to interact strongly with each other. The energy of the DNA kink deformation was estimated as approximately 31 kcal/mol.